Analysis of The Failure in Crude Oil Transmission Pipeline Segment BS CLM–BS CMS PT PQR - Santoso, Teguh; Adrian, Rifki; M, Rizal Fazaul; Cahyono, Rockim Bakti (Universitas Muhammadiyah Yogyakarta, 2025)
The pipeline refers to the API 5L Grade B standard, with a diameter of 8 inches and a length of 212 km. The design life of the pipeline is 20 years. However, after being in operation, it experienced two leak incidents in the same segment within one year. This condition disrupted the oil delivery from PT PQR's field. Therefore, a study is needed to determine the causes of the pipeline's failure before reaching its design life. The investigation involved visual observation of the pipeline samples, pipe thickness testing, chemical composition testing, and microstructural analysis of the leakage area. Additionally, characterization tests were conducted on the elements present in the corrosion product deposits. Process fluid testing was also performed to determine the anion, cation, and scale formation tendency based on Valone & Skillern's guidelines. The results showed visual thinning on the inner surface of the pipeline at the 6 o'clock position. Chemical composition testing revealed no differences from the standard API 5L Grade B composition. SEM analysis in the leakage area identified corrosion morphology caused by dissolved CO2. XRD analysis of the corrosion deposits indicated the presence of siderite (Fe2CO3), hematite (Fe3O4), and iron (Fe) compounds. The pipeline failure occurred due to the presence of corrosive substances, specifically produced water. This condition caused the pipe surface at the 6 o'clock position to be exposed to produced water, initiating the formation of hydrogen ions (H+) and bicarbonate ions (HCO3-).